Brucellosis in camel, small ruminants, and Somali pastoralists in Eastern Ethiopia: a One Health approach - Ahad, Abdullahi Adan; Megersa, Bekele; Edao, Bedaso Mammo (Frontiers in Veterinary Science, 2024)
Brucellosis is a neglected bacterial zoonotic disease with economic and public health importance in pastoral communities of sub-Saharan Africa. A cross-sectional study was conducted from December 2021 to April, 2022 to estimate prevalence and identify the associated risk factors causing brucellosis in animals and associated to occupational diseases in humans from three selected districts of "the Somali Pastoral region", Eastern Ethiopia. In this study, a total of 1000 serum samples were screened for anti-Brucella spp. antibodies using Rose Bengal Plate Test (RBPT) and further confirmed using a competitive Enzyme Linked Immunosorbent Assay (cELISA). A structured questionnaire was used to collect the biodata of tested animals and animal attendants to test the association between explanatory and outcome variables. The overall animal level prevalence was 5 % (95% CI: 6.1-7.2.0) in small ruminants, 2.9% (95 % CI: 1.5-4.9) in camels, and 2.0% (95 % CI: 0.2-3.7) in occupationally linked humans. Herd size and herd history of retained fetal membranes were risk factors associated with Brucella spp. seropositivity in animals (P< 0.05). Disposing of retained fetal membranes was significantly associated (P< 0.05) with Brucella spp. seropositivity in humans. Evidence of brucellosis in various livestock species and associated seropositivity in humans indicates the need for a coordinated One Health approach considering sociocultural dynamics of pastoral communities in controlling brucellosis to safe guard public health and increase livestock productivity.